The mechanism of cryoinjury: In vitro studies on human internal mammary arteries - Müller-Schweinitzer, Else; Brett, Wolfgang; Zerkowski, Hans-Reinhard; Haefeli, Walter E. (British journal of pharmacology, 2000)
The mechanism of cryoinjury was investigated in human internal mammary arteries (IMA) by monitoring contractile responses to ET-1 and KCl.For cryopreservation segments of IMA were equilibrated for 20 min with the cryomedium (RPMI 1640 culture medium containing 1.8 M DMSO and 0.1 M sucrose), frozen at a mean cooling rate of 1.3°C min−1 to −70°C and stored in liquid nitrogen. Before use, samples were thawed slowly and the cryomedium removed by dilution.Compared to unfrozen controls, ET-1 stimulated frozen/thawed IMA with similar efficacy but at 3 fold lower concentrations (P<0.001). Addition of ET-1 (100 nM) induced maximal contraction of unfrozen IMA within 10 min, declining thereafter to 25% after 90 min. In frozen/thawed IMA the ET-1-induced contraction was sustained but could be reversed if protein kinase C was blocked by staurosporine (100 nM). Responses to ET-1 of cryostored IMA were 5 fold more susceptible to blockade by nifedipine than those of controls.After cryostorage the efficacy of KCl was diminished to 40% (P<0.05) and the KCl curve was shifted to the left (2 fold, P<0.001). In both unfrozen and cryostored IMA the KCl (60 mM) effect was sustained and equally susceptible to nifedipine.It is suggested that the smooth muscle cell of IMA is receptive to physical forces which occur during cryopreservation. These forces modify transmembrane signal transduction and intracellular pathways, that are common to pharmacological agonists thereby changing vascular responses to several contractile agonists after thawing.
Gesehen am 26.05.2021